Reconnaissance of prehistoric rock-avalanches and rock blocks slides in the Andean area of Neuquén (37°15′-37°30′S) - Gonzalez Diaz, E.F. (2005)
Five prehistoric rock-avalanches are described in the northern cordilleran region of Neuquén Province, between 37°15′ and 37°30′S and between 70°55′ and 71°05′W. These slides and their deposits were not previously identified and moreover they were classified as glacial and glaciofluvial in origin. All of them are developed on volcanic-sedimentary deposits. They are named after local places: Cerro Piche Moncol, Cerro Guañaco, Cerro Coronal, Laguna Negra and Laguna Lauquen Mallin avalanches. The first three form a group of avalanches situated north of Reñileuvú creek, in the vicinity of the previously described Moncol rock-avalanche. Their break-away zones are located on the lateral slopes of a pre-existing deep glacial valley. The biggest rock-avalanche is the Cerro Piche Moncol and its deposits are due to the collapse of the southern flank of a volcanic edifice with a small caldera. The Cerro Guañaco, Cerro Coronal and Laguna Negra rock-avalanches began as a slump slide to evolving distally into a flow. The slides of Laguna Lauquen Mallín are big rock-block slides. Some local factors, principally contrasting lithology and physical properties, structural factors and more humid conditions during postglacial times favourable conditions for the loss of slope equilibrium. The authors suggest that these gravitational movements triggered by seismic shock. The age of these rock-avalanches is unknown but they must be younger than last local glaciation. © 2005 Asociación Geológica Argentina.